Xây dựng mô hình ra quyết định đổi mới công nghệ cho doanh nghiệp Việt Nam - Nguyễn Đăng , Minh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
The purpose of this study is to develop a scientific management decision-making model and to support the technological innovation decision-making process of Vietnam enterprises. The proposed model is built based on the theoretical basis of "Made in Vietnam Lean Management" decision-making model and from the results of practical research of current decision-making activities on technology renovation of Vietnam enterprises. This research is a valuable reference for not only corporate administrators and researchers on corporate governance in Vietnam in particular, but also in the world in general.
Keywords: Decision-making; Technological Innovation; Made in Vietnam Lean Management